2019
DOI: 10.1021/acsami.9b10705
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Diffusion and Incorporation of Interstitial Oxygen Ions at the TiN/SiO2 Interface

Abstract: Silica based Resistive Random Access Memory (ReRAM) devices have become an active research area due to complementary metal-oxide-semiconductor (CMOS) compatibility and recent dramatic increases in their performance and endurance. In spite of both experimental and theoretical insights gained into the electroforming process,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 88 publications
(237 reference statements)
0
5
0
Order By: Relevance
“…The metal-insulator-metal (MIM) integrated capacitors are key device structures for modern analog and radio frequency integrated circuits [1]. This includes both two-terminal devices such as in ovonic selectors [2], [3], and layered gates in connection with high-κ metal-oxide dielectrics, such as, HfO 2 [4], TiO 2 [5], SiO 2 [6], [7], and Al 2 O 3 [8]. In this scenario, TiN recently become the reference metal for CMOS compatible gates and MIM devices [9].…”
Section: Introductionmentioning
confidence: 99%
“…The metal-insulator-metal (MIM) integrated capacitors are key device structures for modern analog and radio frequency integrated circuits [1]. This includes both two-terminal devices such as in ovonic selectors [2], [3], and layered gates in connection with high-κ metal-oxide dielectrics, such as, HfO 2 [4], TiO 2 [5], SiO 2 [6], [7], and Al 2 O 3 [8]. In this scenario, TiN recently become the reference metal for CMOS compatible gates and MIM devices [9].…”
Section: Introductionmentioning
confidence: 99%
“…Cottom et al [ 29 ] in their theoretical study of the atomistic mechanism of oxygen migration to the interface between amorphous SiO 2 and polycrystalline TiNx, they have shown that the arrival of oxygen atoms at the interface is accompanied by preferential oxidation of undercoordinated Ti sites at the interface, forming a Ti−O layer. Molecular dynamics and spin-polarized density functional theory calculations demonstrate the preferential incorporation of oxygen at defects within the TiN x grain boundaries and their fast diffusion along them.…”
Section: Resultsmentioning
confidence: 99%
“…N vacancies can affect the oxygen diffusion mechanism. It was proposed that the oxygen migrates and occupies the N vacancy site where it is then trapped due to the high energy barrier to be overcome to leave the vacancy site, i.e., 2.0 eV [ 29 ]. In the MIM structures studied, the numerous grain boundaries in the top/bottom electrodes significantly facilitate oxygen diffusion throughout the thickness of TiN x layers, and the nitrogen-vacancy sites trap oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the surface diffusion rate, as well as its behavior, obviously depends on the substrate materials and their surface preparation conditions [23]. Atomistic simulations based on first-principles calculations are often shown to be powerful in estimating the diffusion coefficients [24,25], as recent studies on technologically important surfaces such as TiN and SiO 2 have shown [26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%